Effects of managed forest versus unmanaged forest on physiological restoration from a stress stimulus, and the relationship with individual traits. Issue 2 (4th March 2019) - Saito, Haruo; Horiuchi, Masahiro; Takayama, Norimasa; Fujiwara, Akio
ABSTRACT: "Forest bathing" can evoke positive physiological responses and relieve stress. We investigated how restoration from a stress stimulus is affected by forest management and an individual's personal traits. For the study, we recruited 17 males and took them to either an unmanaged forest (UF) with densely packed trees or a managed forest (MF) with improved light and visibility. We assessed their personality traits and depressive tendencies by the NEO Five-Factor Inventory and Beck Depression Inventory, respectively. The participants performed a static hand grip stress exercise for 2 min at 30% of maximal voluntary contraction, and viewed the forest for 15 min. Their blood pressure (BP) and saliva cortisol increased after the stimulus but then significantly decreased after viewing, with significantly lower levels in the MF than in the UF ( p  < 0.05). Their heart rate (HR) remained unchanged throughout viewing, irrespective of the forest condition. The ratio of low-frequency to high-frequency HR variability, indicative parasympathetic nerve activity, significantly increased by the last 5 min of viewing in the UF ( p  < 0.05), whereas it decreased in the MF. Difference in systolic BP between after the stimulus and after viewing was related to neuroticism and depression scores in the UF, but not in the MF. These findings provide useful information for the future application of forest management and indicate that an MF may have greater beneficial effects than a UF for restoration from physiological stress and that these positive effects may be partly related to individual personal traits.